Academic freedom in Tajikistan: how the suppression, acquiescence and incorporation of intellectuals strengthens the state and affects knowledge production. Issue 4 (2nd October 2021) - Antonov, Oleg; Lemon, Edward; Mullojonov, Parviz
ABSTRACT: While there have been a number of studies of the political economy of knowledge production in Central Asia, the often exploitative relations between foreign and local researcher, there has been less discussion of what Elizabeth Perry recently described as the 'scholar–state' nexus: how authoritarian rule rests on the suppression of independent academics, the 'educated acquiescence' of academia or their incorporation into the 'factory of answers'. Through the concepts of suppression, acquiescence and incorporation, this article examines how restrictions on academic freedom have an impact on knowledge production in Tajikistan.